Apocalypse ; Vision of the Virgin ; Pabasa, Senakulo [videorecording] - Lazaro, Cheche (The Probe Team, 1990)
A report on foretelling the future based on published prophecies. Marian devotees claim the Blessed Virgin Mary has appeared miraculously in Batangas, Quezon City and Loakan, Baguio City. The team looks into some explanations on the apparitions. The team also looks at traditional Filipino Holy Week practices.